Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1074/jbc.m113.511345
|View full text |Cite
|
Sign up to set email alerts
|

Capturing a Reactive State of Amyloid Aggregates

Abstract: Background: Association of redox-active Cu 2ϩ with aggregated A␤ in amyloid plaques has been linked with ROS and oxidative stress in AD. Results: Cu 2ϩ /Cu ϩ -bound A␤ fibrils undergo a redox cycle reaction with ascorbate and oxygen to produce H 2 O 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 91 publications
0
23
0
Order By: Relevance
“…It was generally proposed that production of H 2 O 2 from O 2 occurs directly via a2-electron process without any release of O 2 C À (Scheme 1, mechanism 2). [9,14,18,23,24] This seems coherent, because considering the redox potentials at neutral pH the electron reduction from O 2 to H 2 O 2 is ad own-hill reaction (exergonic), in contrast to the endergonic one-electron reduction of O 2 to O 2 C À .C omputational chemistry supported that Cu I -Ab can activate O 2 to form O 2 C À , [25,26] and that no O 2 C À is released during the H 2 O 2 production (O 2 C À was proposed as an intermediate bound to Cu-Ab). [26] Here,w eu se an electrochemical setup and the specificity of superoxide dismutase-1 (SOD1) to show that the H 2 O 2 production of Cu-Ab proceeds mainly via free O 2 C À as intermediate.T he impact of these findings on ROS production therapeutic approaches in AD is discussed.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…It was generally proposed that production of H 2 O 2 from O 2 occurs directly via a2-electron process without any release of O 2 C À (Scheme 1, mechanism 2). [9,14,18,23,24] This seems coherent, because considering the redox potentials at neutral pH the electron reduction from O 2 to H 2 O 2 is ad own-hill reaction (exergonic), in contrast to the endergonic one-electron reduction of O 2 to O 2 C À .C omputational chemistry supported that Cu I -Ab can activate O 2 to form O 2 C À , [25,26] and that no O 2 C À is released during the H 2 O 2 production (O 2 C À was proposed as an intermediate bound to Cu-Ab). [26] Here,w eu se an electrochemical setup and the specificity of superoxide dismutase-1 (SOD1) to show that the H 2 O 2 production of Cu-Ab proceeds mainly via free O 2 C À as intermediate.T he impact of these findings on ROS production therapeutic approaches in AD is discussed.…”
mentioning
confidence: 83%
“…[21,22] In contrast to the well supported production of H 2 O 2 and HOC,d etection of O 2 C À by nitro blue tetrazolium (NBT) or hydroethidine failed. [9,14,18,23,24] This seems coherent, because considering the redox potentials at neutral pH the electron reduction from O 2 to H 2 O 2 is ad own-hill reaction (exergonic), in contrast to the endergonic one-electron reduction of O 2 to O 2 C À .C omputational chemistry supported that Cu I -Ab can activate O 2 to form O 2 C À , [25,26] and that no O 2 C À is released during the H 2 O 2 production (O 2 C À was proposed as an intermediate bound to Cu-Ab). [9,14,18,23,24] This seems coherent, because considering the redox potentials at neutral pH the electron reduction from O 2 to H 2 O 2 is ad own-hill reaction (exergonic), in contrast to the endergonic one-electron reduction of O 2 to O 2 C À .C omputational chemistry supported that Cu I -Ab can activate O 2 to form O 2 C À , [25,26] and that no O 2 C À is released during the H 2 O 2 production (O 2 C À was proposed as an intermediate bound to Cu-Ab).…”
mentioning
confidence: 99%
“…93 Two binding sites were identified: the Met35 mediating the Fenton reaction through the electron donor sulfide group; 94 and the N-terminal region forming a chelating domain 95 of Asp1, His6, His13 and His14, which undergoes a major structural rearrangement during the redox cycle of ROS production. 96 Interestingly, in vitro experiments have also shown that metal binding noticeably extends the lag time by stabilizing oligomeric and amorphous aggregates, 97 which may explain the poor in vivo detection of the peptide amyloids. Aβ-copper complexes have also been shown to promote lipid peroxidation, in particular within the polyunsaturated chains of membrane lipids, which is another potential toxic mechanism due to neuronal membrane disruption.…”
Section: Aβ Tau and Alzheimer’s Diseasementioning
confidence: 99%
“…H 2 O 2 may react with another reduced metal ion to produce toxic HO radicals through Fenton reaction (Fig. 64 Metal binding elongates the lag phase of fibril formation or stabilizes the oligomeric state. 59 These radical species are said to be involved in lipid and protein peroxidation and finally leading to neuronal death.…”
Section: Oxidative Stressmentioning
confidence: 99%